Synthesis, PtS-type structure, and anomalous mechanics of the Cd(CN)2 precursor Cd(NH3)2[Cd(CN)4]. Issue 21 (15th May 2018) - Coates, Chloe S.; Makepeace, Joshua W.; Seel, Andrew G.; Baise, Mia; Slater, Ben; Goodwin, Andrew L.
Abstract : We report the nonaqueous synthesis of Cd(CN)2 by oxidation of cadmium metal with Hg(CN)2 in liquid ammonia. Abstract : We report the nonaqueous synthesis of Cd(CN)2 by oxidation of cadmium metal with Hg(CN)2 in liquid ammonia. The reaction proceeds via an intermediate of composition Cd(NH3 )2 [Cd(CN)4 ], which converts to Cd(CN)2 on prolonged heating. Powder X-ray diffraction measurements allow us to determine the crystal structure of the previously-unreported Cd(NH3 )2 [Cd(CN)4 ], which we find to adopt a twofold interpenetrating PtS topology. We discuss the effect of partial oxidation on the Cd/Hg composition of this intermediate, as well as its implications for the reconstructive nature of the deammination process. Variable-temperature X-ray diffraction measurements allow us to characterise the anisotropic negative thermal expansion (NTE) behaviour of Cd(NH3 )2 [Cd(CN)4 ] together with the effect of Cd/Hg substitution; ab initio density functional theory (DFT) calculations reveal a similarly anomalous mechanical response in the form of both negative linear compressibility (NLC) and negative Poisson's ratios.